The Impact of Math Game Cards on Third-Grade Students’ Learning Motivation at SDN 2 Sambirejo - Dimas Suprayogo; Dya Ayu Agustiana Putri, M.Pd Dya Ayu Agustiana Putri; Eka Yuliana Sari, M.Pd Eka Yuliana Sari (Primary Education Insight, 2025)
Mathematics is a fundamental discipline in all fields of science, yet many students lack interest in learning it. To address this challenge, innovative and engaging learning media such as mathematics game cards are needed to foster students’ motivation. This study aimed to examine the effect of using game cards as instructional media on the learning motivation of third-grade students at SDN 2 Sambirejo. Employing a quantitative approach with a quasi-experimental design, the study involved 54 students divided into experimental and control groups. Data were analyzed using an independent sample t-test with JAMOVI 2.3.2 software. The pre-test results showed no significant difference in motivation between the two groups (p = 0.152 > 0.05), whereas the post-test results indicated a significant improvement in motivation for students who used the game card media (p < 0.001). These findings suggest that mathematics game cards can significantly enhance students’ learning motivation and serve as an effective alternative to conventional instructional methods.